Nonadaptive host‐use specificity in tropical armored scale insects. Issue 23 (4th November 2020) - Peterson, Daniel A.; Hardy, Nate B.; Morse, Geoffrey E.; Itioka, Takao; Wei, Jiufeng; Normark, Benjamin B.
Abstract: Most herbivorous insects are diet specialists in spite of the apparent advantages of being a generalist. This conundrum might be explained by fitness trade‐offs on alternative host plants, yet the evidence of such trade‐offs has been elusive. Another hypothesis is that specialization is nonadaptive, evolving through neutral population‐genetic processes and within the bounds of historical constraints. Here, we report on a striking lack of evidence for the adaptiveness of specificity in tropical canopy communities of armored scale insects. We find evidence of pervasive diet specialization, and find that host use is phylogenetically conservative, but also find that more‐specialized species occur on fewer of their potential hosts than do less‐specialized species, and are no more abundant where they do occur. Of course local communities might not reflect regional diversity patterns. But based on our samples, comprising hundreds of species of hosts and armored scale insects at two widely separated sites, more‐specialized species do not appear to outperform more generalist species. Abstract : In tropical canopies, we find evidence that diet specialization in armored scale insects might be nonadaptive. Diet generalists occur on more of their potential host plants and are no less abundant than diet specialists.